Monteverdi and the End of the Renaissance - Tomlinson, Gary (Book collections on Project MUSE., 1990)
Combining a close study of Monteverdi's secular works with recent research on late Renaissance history, Gary Tomlinson places the composer's creative career in its broad cultural context and illuminates the state of Italian music, poetry, and ideology in.